Wheelchair-specific fitness of persons with a long-term spinal cord injury: cross-sectional study on effects of time since injury and physical activity level. Issue 12 (4th June 2016) - de Groot, Sonja; van der Scheer, Jan W.; Bakkum, Arjan J. T.; Adriaansen, Jacinthe J. E.; Smit, Christof A.; Dijkstra, Catja; ,; Post, Marcel W. M.; van der Woude, Lucas H. V.
Abstract: Purpose : To study the impact of time since injury (TSI) and physical activity (PA) on fitness of persons with spinal cord injury (SCI). Method : Cross-sectional study. Persons with SCI ( N  = 158) in three TSI strata: 10–19, 20–29 and ≥30 years after SCI and divided in an active and inactive group. Fitness [peak power output (POpeak) and peak oxygen uptake (VO2peak)] was assessed. Results : In persons with tetraplegia, no significant relationship was found between TSI and fitness after controlling for confounders, while a higher activity level was related to a higher POpeak in this group. Active people with tetraplegia also showed less decline in POpeak with an increase in TSI compared to inactive people. In persons with paraplegia, after controlling for confounders, it was shown that TSI had a negative effect on POpeak, while PA was not significantly associated with fitness in people with paraplegia. Conclusions : In people with paraplegia, fitness was significantly lower in those with a longer TSI. Persons with a long TSI might need more attention to remain fit and PA might be an important element in that respect as shown by the results of the group with a tetraplegia. Implications for Rehabilitation: Wheelchair-specific fitness seems to diminish over time after paraplegia. An active lifestyle is related to wheelchair-specific fitness in persons with tetraplegia. Prevention of long-term deconditioning is very important.